1997
DOI: 10.1007/s004200050157
|View full text |Cite
|
Sign up to set email alerts
|

Allergic disease, immunoglobulins, exposure to mercury and dental amalgam in Swedish adolescents

Abstract: High-dose exposure to inorganic mercury in man can influence the immune system and in rare cases cause immune-related disease. Some experimental animals also react with autoimmunity after low doses of inorganic mercury. Glomerulonephritis and an increased formation of immunoglobulin type E (IgE) are characteristic of these reactions. A recent study of 15-year-old adolescents demonstrated an association between immunoglobulin type A (IgA) and mercury concentration in plasma (P-Hg). There was also an association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
3
0
Order By: Relevance
“… Ahlgren et al (2002), Ahlqwist et al (1999), Alanko et al (1996), Apostoli et al (2002), Archbold et al (2004), Athavale et al (2003), Attin et al (1998), Aw et al (2005), Bagedahl‐Strindlund et al (1997), Bailer et al (2001), Bangsi et al (1998), Bellinger et al (2006), Bergdahl et al (1998), Berglund & Molin (1996), Biocina‐Lukenda et al (2004), Blomgren et al (1996), Bratel et al (1996, 1997), Browning et al (1997), Casetta et al (2001), Chong & Pitt (2005), Dalen et al (2003a, 2003b), DeRouen et al (2006), Dohrn & Neuser (2001), Dunne & Abraham (2000), Dunsche et al (2003), Eden et al (2002), Faccioni et al (2003), Factor‐Litvak et al (2003), Fernandes et al (1998), Ganss et al (2000), Gottwald et al (2001), Grandjean et al (1997), Hayashi & Wilson (2003), Henningsson & Sundbom (1996), Herrstrom et al (1996, 1997), Hol et al (2001), Ibbotson et al (1996), Issa et al (2005), Jacobsen & Hensten‐Pettersen (2003), Janson et al (1998), Khamaysi et al (2006), Koch (1999), Kosugi et al (2003), Laeijendecker et al (2004), Laine et al (1997a, 1997b, 1999), Langworth et al (2002), Lindh et al (2001, 2002), Lindow et al (2003), Lopez‐Jornet et al (2004), Luglie et al (2005), Lundin & Rasmusson (2004), Lygre et al (2005), Magnin et al (2003), Malt et al (1997), Marcusson (1996, 1998, 1999), Mehulic et al (2005), Melchart et al (1998), Monaco et al (2001), Nerdrum et al (2004), Osborne & Summitt (1996), Östman et al (1996), Pecegueiro et al (1999), Prochazkova et al (2004), Räsänen et al (1996), Reitemeier et al (2002), Rodvall et al (1998), Santosh et al (1999), Schuster et al (2004), Schuurs et al (2000), Schwartz et al (1998), Stejskal et al (1996), Stenman & Grans (1997), Strömberg et al (1999), Sübay et al (2005), Thornhill et al (2003), Tsuruta et al (2001), Türkün & Aktener (2001), Vamnes et al (2000, 2004), Vilaplana & Romaguera (2000), Wong & Freeman (2003), Yiannias et al (2000). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Ahlgren et al (2002), Ahlqwist et al (1999), Alanko et al (1996), Apostoli et al (2002), Archbold et al (2004), Athavale et al (2003), Attin et al (1998), Aw et al (2005), Bagedahl‐Strindlund et al (1997), Bailer et al (2001), Bangsi et al (1998), Bellinger et al (2006), Bergdahl et al (1998), Berglund & Molin (1996), Biocina‐Lukenda et al (2004), Blomgren et al (1996), Bratel et al (1996, 1997), Browning et al (1997), Casetta et al (2001), Chong & Pitt (2005), Dalen et al (2003a, 2003b), DeRouen et al (2006), Dohrn & Neuser (2001), Dunne & Abraham (2000), Dunsche et al (2003), Eden et al (2002), Faccioni et al (2003), Factor‐Litvak et al (2003), Fernandes et al (1998), Ganss et al (2000), Gottwald et al (2001), Grandjean et al (1997), Hayashi & Wilson (2003), Henningsson & Sundbom (1996), Herrstrom et al (1996, 1997), Hol et al (2001), Ibbotson et al (1996), Issa et al (2005), Jacobsen & Hensten‐Pettersen (2003), Janson et al (1998), Khamaysi et al (2006), Koch (1999), Kosugi et al (2003), Laeijendecker et al (2004), Laine et al (1997a, 1997b, 1999), Langworth et al (2002), Lindh et al (2001, 2002), Lindow et al (2003), Lopez‐Jornet et al (2004), Luglie et al (2005), Lundin & Rasmusson (2004), Lygre et al (2005), Magnin et al (2003), Malt et al (1997), Marcusson (1996, 1998, 1999), Mehulic et al (2005), Melchart et al (1998), Monaco et al (2001), Nerdrum et al (2004), Osborne & Summitt (1996), Östman et al (1996), Pecegueiro et al (1999), Prochazkova et al (2004), Räsänen et al (1996), Reitemeier et al (2002), Rodvall et al (1998), Santosh et al (1999), Schuster et al (2004), Schuurs et al (2000), Schwartz et al (1998), Stejskal et al (1996), Stenman & Grans (1997), Strömberg et al (1999), Sübay et al (2005), Thornhill et al (2003), Tsuruta et al (2001), Türkün & Aktener (2001), Vamnes et al (2000, 2004), Vilaplana & Romaguera (2000), Wong & Freeman (2003), Yiannias et al (2000). …”
Section: Methodsmentioning
confidence: 99%
“…Ahlgren et al (2002),Ahlqwist et al (1999),Alanko et al (1996),Apostoli et al (2002),Archbold et al (2004),Athavale et al (2003),Attin et al (1998),Aw et al (2005),Bagedahl-Strindlund et al (1997),Bailer et al (2001),Bangsi et al (1998), Bellinger et al (2006,Bergdahl et al (1998),Berglund & Molin (1996),Biocina-Lukenda et al (2004),Blomgren et al (1996),Bratel et al (1996Bratel et al ( , 1997,Browning et al (1997), Casetta et al (2001), Chong & Pitt (2005), Dalen et al (2003a, 2003b), DeRouen et al (2006), Dohrn & Neuser (2001), Dunne & Abraham (2000), Dunsche et al (2003), Eden et al (2002), Faccioni et al (2003), Factor-Litvak et al (2003), Fernandes et al (1998), Ganss et al (2000),Gottwald et al (2001),Grandjean et al (1997),Hayashi & Wilson (2003),Henningsson & Sundbom (1996),Herrstrom et al (1996Herrstrom et al ( , 1997,Hol et al (2001),Ibbotson et al (1996),Issa et al (2005),Jacobsen & Hensten-Pettersen (2003),Janson et al (1998),Khamaysi et al (2006),Koch (1999),Kosugi et al (2003),Laeijendecker et al (2004),Laine et al (1997aLaine et al ( , 1997bLaine et al ( , 1999,Langworth et al (2002),…”
mentioning
confidence: 99%
“…A Swedish study found a statistically significant correlation between immunoglobulin type A (IgA) and plasma mercury concentration, but no correlation of plasma mercury with IgE in 15-year olds (Herrstrom and Hogstedt, 1994). A follow-up study in 19-year old students (n ¼ 77), half with allergic diseases (asthma, allergic rhinitis, eczema), provided no confirmation of the correlation between IgA and plasma mercury concentration (Herrstrom et al, 1997). There was also no association of plasma mercury concentration with IgE or with allergic disease, but a correlation with IgG 2 was found (r ¼ 0.33, P ¼ 0.003).…”
Section: Effects On Immunologic Functionmentioning
confidence: 99%